The Circular Economy of Dharavi - Sourav Dey; Lisa Domenica Iulo (Enquiry: The ARCC Journal of Architectural Research, 2021)
As developing nations continue to progress, people of these countries face problems of shortages in building materials and rising production of solid waste. The purpose of this research study is to explore the potential of establishing a circular economy by recycling/reusing solid waste as alternative building materials. Focused on the slum of Dharavi in Mumbai, a settlement well-known for its existing recycling business, this article explores the concept of a circular economy utilizing local informal labor by considering the flow of waste materials in the slum. This article presents an analysis of the case studies where waste is reused as a building product and identifies the gaps, advantages, and disadvantages related to how and where the building materials from the case studies could be adapted in the context of the Dharavi slum.